Knowledge and practices related to sexually transmitted infections among women of reproductive age living in Katanga slum, Kampala, Uganda - Nawagi, Faith (Afr Health Sci, 2016)
BACKGROUND: Sexually transmitted infections (STIs) still stand as one of the commonest health problems affecting women of reproductive age. The knowledge and practices of STIs, among susceptible populations such as women of reproductive age, living in slums like Katanga in Kampala Uganda need to be established. METHODS: This was a cross-sectional study with 339 participants in Katanga slum. Data was collected using an interviewer administered questionnaire, entered and analysed using SPSS version 17.0. Data was summarized using frequencies for categorical data and medians for continuous data. RESULTS: Majority of the participants (71.9%) were ≥25years with a mean age of 28.0(SD ±7.0) years. The commonest symptoms known to the participants were genital itching (60%) and genital rash (14.5%). Most mentioned multiple partners (63.7%) and unprotected sex (50.7%) as predisposing factors to STIs. Knowledge on methods of prevention was high (92.3%) however, 18.8% were found positive for STIs using the syndromic approach and 82% mentioned having suffered from STIs in the past 6 months more than once. CONCLUSION: Most participants did not know about the systemic effects of STIs to their health and didnot follow the appropriate behavior patterns despite being knowledgeable about the various methods of prevention of STIs.